In memory of Moisey Isaakovich Kaganov - Bakai, O.S.; Bazaliy, Ya.B.; Yu, Lu (Вопросы атомной науки и техники, 2019)
Professor Moisey Isaakovich Kaganov passed away at the age of 99 on August 31, 2019. He
was a prominent theoretical physicist, a talented promoter of science, and an extraordinary personality